The courage of faith : Martin Luther and the theonomous self - Gaebler, Mary (Mary D.) (Minneapolis Fortress Press, 2013)
"Luther's thinking about will and agency evolved over his lifetime. His anthropology became increasingly open, with a growing affirmation of the created order and the recognition of faith's role in the transformation of the world, leading to Luther's exhortation to take courage in Gods transforming presence for the good of all" -- Publisher description.
Includes bibliographical reference and index.
Keywords: Luther, Martin, -- 1483-1546.; Luther, Martin, -- 1483-1546.; Theological anthropology; Faith; Faith; Theological anthropology